Academic Peer Detailing—The Preparation and Experience of Detailers Involved in a Project to Disseminate a Comparative Effectiveness Module. Issue 2 (2016) - Morrow, Robert W.; Tattelman, Ellen; Purcell, Jennifer M.; King, Jason; Fordis, Michael
Abstract : Introduction: Academic detailing uses communication skills, relationship building, and feedback to facilitate behavior change. This report, part of a larger initiative to disseminate evidence summaries of systematic reviews, demonstrates the feasibility of disseminating a comparative effectiveness module to physicians using peer detailers and examines the development of faculty for this process. We describe planning and implementation of a train-the-detailer session, detailer reactions to the process, and results of the dissemination project. Methods: We recruited 10 experienced primary care clinical faculties in Family and Social Medicine at the Albert Einstein College of Medicine. Detailers attended a 90-minute train-the-detailer session and detailed 150 practitioners at community practices. We evaluated the experiences of the learners and detailers with questionnaires, a focus group, and individual interviews of the detailers. Results: The experiences of detailing in different contexts were uniformly positive. Learners felt the materials were valuable, and that they would implement them or already had implemented them. In the postsurvey completed by 65 of the 150 detailed learners, 97% percent stated that they changed their practice or had already incorporated the practice change before the detailing. All detailers reported a change in their own practice. Detailers found the teaching materials and detailers' guide helpful. Some initially expressed a concern about not knowing enough, which lessened with detailing experience. Discussion: Peer detailing seems doable and well received, especially with the availability of high quality, previously prepared, and tested evidence-based content and materials. Detailers were easily recruited and trained to apply their teaching skills in this new format. The amount of time spent in training sessions on detailing training as opposed to content mastery can be adjusted depending on faculty needs.